STRATEGI KOMUNIKASI KOMISI PEMILIHAN UMUM (KPU) KOTA PEKANBARU DALAM MENSOSIALISASIKAN PEMILIHAN UMUM 2014 - Julia, Rafika; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Based on data from the General Election Commission (KPU) Riau province, the level of participation community in the city of Pekanbaru only reached 55.64% of the total number of people registered in Pekanbaru city DPT. The purpose of this study to determine the strategy, target recognition media selection strategy, objectives and strategy evaluation strategy roles message communicator that is used by the General Elections Commission (KPU) Pekanbaru. The research used a qualitative descriptive methods and data are grouped based on the fact collected by field observation, maintenance and documentation. Informants in this research was 12 people were taken by purposive sampling technique. Interactive data analysis model that use the results of the research are described in the data analysis and checking the validity of the data that the researchers use participatory techniques and triangulation. The results showed that the communication from the Commission concerning the introduction of Pekanbaru, the whole community Pekanbaru registered as voters and target to target position is divided into five segments are strategic voters, religious groups, women's groups, people with disabilities and marginalized groups. After the election of the media are divided into groups and the media, so the media all levels of society can achieve. The content of the message delivered by the election of Pekanbaru is the message compelling, educational and informative. In doing a variety of activities for the 2014 election socialize, Pekanbaru election commission not only work, but formed a team Relationship electoral commission as supported from Pekanbaru to disseminate to the public the 2014 election on the basis of each segment. Communication Strategies that the Commission in Pekanbaru, was very effective visible from the increasing participation of 7% compared to the previous period.Keyword: strategy, communication, socialize